Prediction of colorectal cancer diagnosis based on circulating plasma proteins. Issue 9 (7th August 2015) - Surinova, Silvia; Choi, Meena; Tao, Sha; Schüffler, Peter J; Chang, Ching‐Yun; Clough, Timothy; Vysloužil, Kamil; Khoylou, Marta; Srovnal, Josef; Liu, Yansheng; Matondo, Mariette; Hüttenhain, Ruth; et al.
Abstract: Non‐invasive detection of colorectal cancer with blood‐based markers is a critical clinical need. Here we describe a phased mass spectrometry‐based approach for the discovery, screening, and validation of circulating protein biomarkers with diagnostic value. Initially, we profiled human primary tumor tissue epithelia and characterized about 300 secreted and cell surface candidate glycoproteins. These candidates were then screened in patient systemic circulation to identify detectable candidates in blood plasma. An 88‐plex targeting method was established to systematically monitor these proteins in two large and independent cohorts of plasma samples, which generated quantitative clinical datasets at an unprecedented scale. The data were deployed to develop and evaluate a five‐protein biomarker signature for colorectal cancer detection. Synopsis: A five‐protein biomarker signature discovered and validated by mass spectrometry can accurately predict colorectal cancer (CRC) diagnosis non‐invasively from a blood sample. Secreted protein biomarker candidates discovered in tumor tissue were detected in the circulation of healthy and CRC subjects. A five‐protein predictive diagnostic signature was developed in a cohort of 100 healthy and 100 CRC subjects, and independently validated in an external cohort of 67 healthy and 202 CRC subjects. The protein biomarker signature was found to be more effective for CRC subjects with larger tumors. Abstract : A five‐protein biomarker signature discovered and validated by mass spectrometry can accurately predict colorectal cancer (CRC) diagnosis non‐invasively from a blood sample.